EVALUATION OF EFFICIENT USE OF INVESTMENT IN THE PRODUCTION OF MANUFACTURED METAL GOODS IN EXCEPT MACHINERY AND EQUIPMENT - Usmanov Bakhtiyor (Journals Park Publishing, 2022)
This article examines the areas of effective use of investments in the production of finished metal products, in addition to machinery and equipment, and analyzes the methods of evaluating these processes. Priorities for investment are assessed by an expert method. It also proposes authorial approaches to the scientific study of problems related to the efficient use of investments and the improvement of investment efficiency.
Keywords: investor; investment; efficiency